Design of Web-Based Warehouse Information System - Rian, Hesti; Gustiawan, Handa; Liansyah, Akbar Ramadhan (Jurnal Teknologi Informatika dan Komputer, 2025)
Basically, a company engaged in manufacturing requires adequate warehouse inventory management to support every job done, especially when the work is still done manually. Every item that comes out of stock is recorded on a card, then later monitored whether it matches the records on the card with the inventory in the warehouse. The purpose of this study is to design a web-based information system as a solution to problems arising from manual data processing. The data collection method used by the author is a literature study and field study. Data collection that covers all goods to fulfill each business process is still done manually which causes many errors or discrepancies between the available data and the existing goods. Another obstacle, because the data collection is still done manually, causes the re-data collection process on existing data to take time, because the search for the required data must be searched for one by one. This study identifies in detail the deficiencies that occur in the warehouse storage management process starting from the mismatch between the recorded stock of goods and the physical stock of goods, the data search process is also hampered and inefficient and tends to be time consuming because the data is searched manually, and there is inaccuracy in the reporting of warehouse goods so that it disrupts the work process. With the Design of this Warehouse Information System, it is expected to be a Solution to the existing problems.